Peran Market Timing Ekuitas, dan Strategi Korporasi dalam Menentukan Struktur Modal Perusahaan - Aditya Achmad Rakim (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2018)
The purpose of this study is to corporate strategies in terms of liquidity and growth is expected to increase the confidence of shareholders upon issuance of equity so that the firm has a low capital structure. Population data used are the financial statements of the companies listed in the Index IHSG period 2009-2017. The results of the analysis of the data rights issue period 2010-2016 shows that the equity market timing and capital structure is not supported. The test results influence the interaction between equity market timing and liquidity to capital structure shows that the higher of liquidity of the company has higher leverage. Meanwhile, companies that issue stock when prices are high and have a high asset growth, the company has a capital structure that is low as high.